1048 In Vitro Evaluation of the Response of Human Tendon-Derived Stromal Cells to a Novel Electrospun Suture. (19th August 2022) - Nezhentsev, A; Abhari, R; Baldwin, M; Mimpen, J; Augustyniak, E; Isaacs, M; Mouthuy, PA; Carr, A; Snelling, S
Abstract: Aim: Recurrent tears after surgical tendon repair remain common, with 40% of rotator cuff repairs failing within one year. Repair failures can be partly attributed to the use of sutures not designed for the tendon cellular niche. Synthetic electrospun materials can mechanically support the tendon while providing topographical cues that modulate the immune response to promote wound healing. Here, a novel electrospun suture made from twisted polydioxanone (PDO) polymer filaments is compared to PDS II, a PDO suture clinically utilised in tendon repair. Method: We evaluated the ability of electrospun suture and PDS II to support the attachment and proliferation of human tendon-derived stromal cells using PrestoBlue cell viability assays and scanning electron microscopy. Suture surface chemistry was analysed using X-ray photoelectron spectroscopy (XPS). Bulk RNA-Seq interrogated the transcriptional response of primary tendon-derived stromal cells to sutures after 14 days. Results: The electrospun suture showed increased initial cell attachment compared to PDS II. XPS revealed that both sutures had similar local surface chemistry, indicating that the tendon-like architecture of electrospun suture was responsible for the greater cell attachment. Furthermore, electrospun suture elicited a stronger transcriptional response compared with PDS II, with relative enrichment of pathways including mTorc1 signalling and depletion of epithelial-to-mesenchymal transition and extracellular matrix gene sets. Neither suture induced transcriptional upregulation of inflammatory pathways. Conclusion: Twisted electrospun sutures show promise in improving outcomes in surgical tendon repair by allowing increased cell attachment while maintaining a tissue response indicative of cell proliferation and wound healing, without significant fibrosis.